Telomere length shows no association with BRCA1 and BRCA2 mutation status. - Emma Killick (Public Library of Science (PLoS), 2014)
This study aimed to determine whether telomere length (TL) is a marker of cancer risk or genetic status amongst two cohorts of BRCA1 and BRCA2 mutation carriers and controls. The first group was a prospective set of 665 male BRCA1/2 mutation carriers and controls (mean age 53 years), all healthy at time of enrollment and blood donation, 21 of whom have developed prostate cancer whilst on study. The second group consisted of 283 female BRCA1/2 mutation carriers and controls (mean age 48 years), half of whom had been diagnosed with breast cancer prior to enrollment. TL was quantified by qPCR from DNA extracted from peripheral blood lymphocytes. Weighted and unweighted Cox regressions and linear regression analyses were used to assess whether TL was associated with BRCA1/2 mutation status or cancer risk. We found no evidence for association between developing cancer or being a BRCA1 or BRCA2 mutation carrier and telomere length. It is the first study investigating TL in a cohort of genetically predisposed males and although TL and BRCA status was previously studied in females our results don't support the previous finding of association between hereditary breast cancer and shorter TL.